EXTH-43. GENERATION OF A B-CELL-BASED VACCINE FOR THE TREATMENT OF GLIOBLASTOMA. (9th November 2020) - Lee Chang, Catalina; Miska, Jason; Hou, David; Rashidi, Aida; Zhang, Peng; Burga, Rachel; Torres, Ignacio Jusue; Xiao, Ting; Arrieta, Victor; Zhang, Daniel; Lopez-Rosas, Aurora; Han, Yu; et al.
Abstract: Immunotherapy has revolutionized the treatment of many tumors. However, most glioblastoma (GBM) patients have not, so far, benefited from such successes. With the goal of exploring ways to boost anti-GBM immunity, we developed a B-cell-based vaccine (BVax ) that consists of 4-1BBL + B cells activated with CD40 agonism and IFNg stimulation. BVax migrate to key secondary lymphoid organs and are proficient at antigen cross-presentation, which promotes both the survival and functionality of CD8 + T cells. A combination of radiation, BVax, and PD-L1 blockade conferred tumor eradication in 80% of treated tumor-bearing animals. This treatment elicited immunologic memory that prevented the growth of new tumors upon subsequent re-injection in cured mice. GBM patient-derived BVax were successful in activating autologous CD8 + T cells; these T cells showed a strong ability to kill autologous glioma cells. In addition to the role in activating CD8 + T cells, BVax produce tumor-specific antibodies able to control tumor growth via antibody-mediated cell cytotoxicity. In conclusion, BVax tackles GBM immunosurveillance escape by using both cellular (CD8 + T-cell activation) and humoral (anti-tumor antibody production) immunity. Our study provides an efficient alternative to current immunotherapeutic approaches that can be readily translated to the clinic.